Polystoma viridis Euzet, Combes et Batchvarov, 1974 (Monogenea, Polystomatidae) — новый вид в фауне СССР - Пароконный, А.С.; Шарпило, В.П.; Лисицына, О.И. (Вестник зоологии, 1981)
The paper deals with an illustrated description of Polystoma viridis, a new species: in the USSR fauna which parasite of Bufo viridis Laur. The new species was found in some places of the USSR European part. The species has certain morphological distinctions as compared with P. integerrimum which was erroneously considered earlier a parasite not only of frogs but also of toads.